On the synthesis of the carboxylated graphene via graphene oxide liquid-phase modification with alkaline solutions. (December 2020) - Ryzhkov, S A; Rabchinskii, M K; Shnitov, V V; Baidakova, M V; Pavlov, S I; Kirilenko, D A; Brunkov, P N
Abstract: In this work we present a facile method for the synthesis of the carboxylated graphene derivate. The resulting material contains up to 10.9 at.% of carboxyl groups and with negligible content of other oxygen-containing groups. Moreover, formation of large round-shaped nanoscale holes is observed due to the applied synthesis process. The synthesized graphene derivative is of high interest for the sensing applications due to combination of its conductive nature and chemical reactivity provided by the attached carboxyl groups.